2010
DOI: 10.1093/molehr/gaq073
|View full text |Cite
|
Sign up to set email alerts
|

In human granulosa cells from small antral follicles, androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA

Abstract: Human small antral follicles (diameter 3-9 mm) were obtained from ovaries surgically removed for fertility preservation.From the individual aspirated follicles, granulosa cells and the corresponding follicular fluid were isolated in 64 follicles, of which 55 were available for mRNA analysis (24 women). Expressions of androgen receptor (AR) mRNA levels in granulosa cells, and of androstenedione and testosterone in follicular fluid, were correlated to the expression of the FSH receptor (FSHR), LH receptor (LHR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 31 publications
6
80
1
8
Order By: Relevance
“…Thus, these tests do not ideally reflect the pool of unrecruited follicles, which may be responsible for ovulatory cycles and the long-term reproductive potential [25][26][27][28]. Age, menstrual cycle length, basal serum FSH, basal estradiol, clomiphene citrate challenge test, AFC, ovarian volume, and ovarian blood flow had been reported to evaluate ovarian reserve, but we need more markers to make the cycle cheaper and more likely to be successful [29][30][31][32][33][34]. In this study, we find that basal T level correlates with AFC and basal FSH levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these tests do not ideally reflect the pool of unrecruited follicles, which may be responsible for ovulatory cycles and the long-term reproductive potential [25][26][27][28]. Age, menstrual cycle length, basal serum FSH, basal estradiol, clomiphene citrate challenge test, AFC, ovarian volume, and ovarian blood flow had been reported to evaluate ovarian reserve, but we need more markers to make the cycle cheaper and more likely to be successful [29][30][31][32][33][34]. In this study, we find that basal T level correlates with AFC and basal FSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…COH is an essential part of IVF and is needed to obtain oocytes that can be fertilized in vitro. The high cost of IVF is partly due to the use of expensive drugs, such as gonadotrophins, needed for COH [34,35]. In clinical practice, physicians often rely on clinical experience and personal judgment when selecting an appropriate starting dose of follicle stimulation hormone (FSH).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in human GCs from small antral follicles has reported a positive correlation between mRNA levels of AR and FSHR and androgen levels in follicular fluid (Nielsen et al 2011). Furthermore, androgens were found to induce FSHR mRNA expression during pre-antral to antral follicle progression in several animal models, such as primates , Weil et al 1999, gilts , and bovine (Luo & Wiltbank 2006).…”
Section: Androgens and Follicle-stimulating Hormone Receptormentioning
confidence: 95%
“…AR expressed on ovarian granulosa cells in several mammalian species, most abundantly in pre-and early antral ovarian follicles and gradually declined upon maturation of the ovarian follicle [20]. Recent studies on both human and animals models underlines the importance of AR in follicle growth and survival, FSH mediated dominant follicle selection and conversion of androgens to estrogens in granulosa cell and its impact on its altered expressions [21,22]. Differential expressions of AR at different stages of folliculogenesis, implies the essential role of this receptor on normal functions of ovary.…”
Section: Discussionmentioning
confidence: 99%